THE VALUE OF SCHOOL LIBRARIES IN WEST BENGAL AND THEIR CONTEMPORARY SERVICES (LIS TODAY, 2023)
To assist and support the school's instructional endeavours, the library is kept up. It  might be useful for students' academic and extracurricular endeavours. There are primary,  middle, and secondary levels in the school library. This paper has covered the goals, duties,  contemporary services, and significance of secondary school libraries. In the present era, a  computer system connected to a network is required for the school library. For kids and  instructors to adjust to today's more advanced technology, a contemporary school library  and its new services are crucial.
Keywords: School Library; Stock verification; Importance of School Library; Modern Services of School Library